The Effect Of Family Support And Organizational Support On The Professionalism Of Personnel Of The Lampung Regional Police Ditpamobvit With Work-Life Balance As A Mediation Variable: English - Febriandini, Fina; Febrianty; Pratama, Rezahardian (International Journal of Technology and Education Research, 2026)
This study aims to examine the influence of family support and organizational support on the professionalism of Ditpamobvit personnel at Polda Lampung, with Work-life balance as a mediating variable. The professionalism of police personnel is a crucial factor in achieving quality and trustworthy service, influenced by various aspects in both the work environment and family life. Family support provides a strong emotional foundation, while organizational support offers the means and conducive environment for enhancing performance and professionalism. This research employs a quantitative method using a survey approach and purposive sampling technique. Data were collected through questionnaires and analyzed using path analysis to test the direct relationships and the mediating role of work-life balance. The results indicate that family and organizational support significantly affect personnel professionalism, both directly and through improving work-life balance. Work-life balance acts as a mediating variable that strengthens this relationship by balancing the demands of work and personal life of police personnel. This study contributes theoretically and practically to human resource management policy development in the police force, with implications for improving public service quality and personnel welfare. The findings are expected to support decision-making that fosters sustainable and integrity-based police professionalism